Translation Strategies in the Indonesian Version of We Love Disney Album - Erlinda Suryaning Giri; Ivonne Muliawati Harsono (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This qualitative study discusses the translation strategies in the Indonesian version of We Love Disney album using Baker’s (2018) theory. This study analyzes the chorus of each song from the album to disclose the translation strategies employed in the translation of the twelve English songs from the We Love Disney album into the Indonesian version, along with the suitability of the strategies in terms of meaning and form. The writers used seven out of eight translation strategies by Baker (2018).The findings show that the translator used translations by a more general word, more neutral/less expressive word, paraphrase using related word, paraphrase using unrelated word, and omission. Moreover, the strategies were accurately used in terms of meaning in more than half of the data. In terms of form, nine out of twelve songs failed to meet both rhymes and syllables requirements.